2013
DOI: 10.1186/1475-2875-12-171
|View full text |Cite
|
Sign up to set email alerts
|

G6PD deficiency in Plasmodium falciparum and Plasmodium vivax malaria-infected Cambodian patients

Abstract: BackgroundGlucose-6-phosphate-dehydrogenase deficiency (G6PDd) rates are unknown in malaria-infected Cambodian patients. These data are key to a rational drug policy for malaria elimination of Plasmodium falciparum and Plasmodium vivax.MethodsFrom September 2010–2012, a two-year survey of G6PDd and haemoglobinopathies assessed by quantitative enzyme activity assay and haemoglobin electrophoresis, respectively, was conducted in malaria-infected patients presenting to 19 health centres throughout Cambodia.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 22 publications
5
43
2
4
Order By: Relevance
“…Participants with G6PDd showed lower levels of hemoglobin than participants with normal G6PD. Although a previous study on the Cambodian population found that G6PDd was associated with lower hemoglobin levels (33) , we could discern no clear relationship between G6PDd and hemoglobin levels in the present study. However, in another study, Satyagraha et al (34) found that G6PDd was associated with higher hemoglobin levels, whereas, in contrast, other studies have found no correlation between G6PDd and hemoglobin levels (35) (36) .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Participants with G6PDd showed lower levels of hemoglobin than participants with normal G6PD. Although a previous study on the Cambodian population found that G6PDd was associated with lower hemoglobin levels (33) , we could discern no clear relationship between G6PDd and hemoglobin levels in the present study. However, in another study, Satyagraha et al (34) found that G6PDd was associated with higher hemoglobin levels, whereas, in contrast, other studies have found no correlation between G6PDd and hemoglobin levels (35) (36) .…”
Section: Discussioncontrasting
confidence: 55%
“…There is no clear explanation to account for the low sensitivity to malaria infection. The level of enzyme activity does not seem to be the main factor responsible: this study and previous studies have shown no signifi cant difference in enzyme activity between individuals with and without malaria infection (20) (33) . This may be due to intrinsic characteristics of the parasite that somehow affect the chemistry of Carestart™ G6PD, leading to a decrease in sensitivity.…”
Section: Discussionmentioning
confidence: 79%
“…In Cambodia, approximately 90 % of G6PDd is due to the Viangchan variant, which has a median enzyme activity of 0.8 U/gHb (~7 % of the population median of 12 U/gHb), placing it at the severe end of the G6PDd spectrum [39, 40]. AHA induced by 15 mg of daily PQ alone was well tolerated in healthy Cambodian Air Force men who had a mean baseline haemoglobin concentration of approximately 14 g/dL and which fell by a mean of 21 % on day (D)7, persisting to D15 [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, nine studies whose data either cannot be extracted, overlapped, or combined with the rest of the data, and thus were excluded. Among the 30 included studies, the species of Plasmodium are only Plasmodium falciparum in 17 studies3571011181920212223242526272829, only Plasmodium vivax in one study30, and combined species ( P. falciparum with P. vivax, P. falciparum with P. malariae, P. vivax with P. malariae , and P. falciparum with P. vivax and P. malariae ) in eight studies1415313233343536. Jalloh 200432, Tantular 199936, and Kruatrachue 196215 reported separate data for P. vivax which meta-analyzed with that of Leslie 201030.…”
Section: Resultsmentioning
confidence: 99%